Complementary and Alternative Medicine Ethics, the Patient, and the Physician - Snyder, Lois (Biomedical Ethics Reviews, 2007)
Complementary and Alternative Medicine examines the real-life implications of patient issues and the healthcare system in which care is delivered. Because complementary and alternative medicine (CAM) are not presently considered to be a part of conventional medicine, this book discusses the effect that CAM has on patients, physicians, healthcare, and policymakers. Also included are the implications that CAM has on traditional patient-physician relationships as well as the physician's ethical obligations on this subject.